PENGARUH SOSIALISASI PAJAK, SANKSI PAJAK DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KECAMATAN TAMBUN SELATAN - Muh Farhan Yudamahendra; Uswatun Khasanah; Maidani Maidani (Jurnal Ilmiah Akuntansi, 2026)
This study aims to examine the effect of tax socialization, tax sanctions, and tax rates on individual taxpayer compliance in South Tambun District. This study uses primary data collected through questionnaires distributed to individual taxpayers in South Tambun District. The sample was determined using a purposive sampling method, with a total of 101 respondents. The data were analyzed using Smart PLS 4.1 software. The results indicate that tax socialization does not have a positive effect on taxpayer compliance, while tax sanctions and tax rates have a positive effect on taxpayer compliance.